POTENSI DAN PEMANFAATAN LIMBAH PRODUKSI PANGAN DAN KEONG MAS SEBAGAI PERANGKAP Leptocorisa sp. PADA TANAMAN PADI - Ningsih, Sulistia; Sari, Dahlia Wulan (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
In Indonesia, Leptocorisa sp. is one of the pests that can cause a yield reduction of up to 50%. Control is generally carried out using chemical insecticides which can have a negative impact. Therefore it is necessary to look for control alternatives that are safe and environmentally friendly. This study aims to determine the type and height of bait traps that are most effective in controlling stink bugs on rice plants. Four replications of a factorial Randomized Block Design (RBD) were utilized in this investigation. According to the findings of the observations, there are on average 7.0 individuals of Leptocorisa sp., the most attracted golden snail bait, with a height of 20 cm above the rice plant. Leptocorisa sp. attack intensity. The highest was in the pineapple skin bait trap treatment with a range of 14.0-19.9%, while the lowest was in the golden snail bait trap treatment with a range of 1.1-2.6%. The installation of bait traps should be done at the right generative phase of the rice plant, to obtain effective results.